2022
DOI: 10.2967/jnumed.121.263448
|View full text |Cite
|
Sign up to set email alerts
|

The PRIMARY Score: Using intra-prostatic PSMA PET/CT patterns to optimise prostate cancer diagnosis.

Abstract: BackgroundMulti-parametric magnetic resonance imaging (mpMRI) is validated for the diagnosis of clinically significant prostate cancer (csPCa). 68 Ga-PSMA -11 PET/CT (PSMA-PET/CT) combined with mpMRI has improved negative predictive value over mpMRI alone for csPCa. The aim of this post-hoc analysis of the PRIMARY study was to evaluate the clinical significance of patterns of intra-prostatic PSMA activity, proposing a 5-point PRIMARY score to optimise accuracy of PSMA-PET/CT for csPCa in a low prevalence popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 24 publications
5
64
1
1
Order By: Relevance
“…The specific patterns were described as follows: Pattern A, defined as diffuse transition zone (TZ) activity if centrally placed within the prostate, with no PSMA activity extending to the edge of the prostate margin; Pattern B, symmetrical central zone (CZ) activity with no PSMA activity extending to the prostate margin; Pattern C, focal TZ activity defined visually as more than twice background TZ activity; Pattern D, focal peripheral zone (PZ) activity. Table 7 shows the 5-point PRIMARY score classification [ 13 ].…”
Section: Research Strategy Resultsmentioning
confidence: 99%
“…The specific patterns were described as follows: Pattern A, defined as diffuse transition zone (TZ) activity if centrally placed within the prostate, with no PSMA activity extending to the edge of the prostate margin; Pattern B, symmetrical central zone (CZ) activity with no PSMA activity extending to the prostate margin; Pattern C, focal TZ activity defined visually as more than twice background TZ activity; Pattern D, focal peripheral zone (PZ) activity. Table 7 shows the 5-point PRIMARY score classification [ 13 ].…”
Section: Research Strategy Resultsmentioning
confidence: 99%
“…At present, prostate biopsy was still the gold standard for the diagnosis of PCa, but there was a certain rate of missed diagnosis in puncture biopsy, and there were also complications after puncture. Meissner and Louise et al (31,32)recently reported that among patients highly suspected of PCa in MPMRI and PSMA-PET, patients with strong uptake of PSMA and MRI positive could avoid definitive biopsy and directly conduct definitive treatment. Avoiding prostate biopsy before RP might be an effective choice.…”
Section: Discussionmentioning
confidence: 99%
“…Meissner and Louise et al. ( 31 , 32 )recently reported that among patients highly suspected of PCa in MPMRI and PSMA-PET, patients with strong uptake of PSMA and MRI positive could avoid definitive biopsy and directly conduct definitive treatment. Avoiding prostate biopsy before RP might be an effective choice.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will determine whether biopsy may be safely omitted in men with high clinical suspicion of clinically significant prostate cancer with negative combined imaging 13 . Although PI‐RADS scoring has long been used for MRI, recent research has led to the development of a standardised reporting system for PSMA PET/CT, with research ongoing 32,33 . PSMA PET/CT may suit men unable to have mpMRI prostate due to metallic foreign bodies or implants, as localisation with PSMA PET/CT can assist lesion targeting at biopsy.…”
Section: Early Detection Of Prostate Cancer: Advances To Reduce Overd...mentioning
confidence: 99%
“… 13 Although PI‐RADS scoring has long been used for MRI, recent research has led to the development of a standardised reporting system for PSMA PET/CT, with research ongoing. 32 , 33 PSMA PET/CT may suit men unable to have mpMRI prostate due to metallic foreign bodies or implants, as localisation with PSMA PET/CT can assist lesion targeting at biopsy.…”
Section: Early Detection Of Prostate Cancer: Advances To Reduce Overd...mentioning
confidence: 99%